Implementasi Kebijakan Imunisasi Dasar Lengkap Pada Balita di Puskesmas Polak Pisang Kabupaten Indragiri Hulu - Virna Museliza; Sitti Rahmah; Novi Supiani T; Candra Jon Asmara (Policy, Law and Political Research Center, 2026)
Complete basic immunization is a health policy that is important for reducing morbidity, disability, and mortality rates among children under five caused by diseases preventable through immunization. However, immunization coverage at the primary healthcare service level still shows fluctuations and disparities due to the lack of parental knowledge, trust in the benefits, and fear of the effects of basic immunization. This study aims to analyze the implementation of the complete basic immunization program policy for children under five at the Polak Pisang Community Health Center, Indragiri Hulu Regency. The study used a qualitative descriptive approach with data collection through observation, in-depth interviews, and documentation involving ten informants. Data analysis was carried out interactively by referring to George C. Edwards III’s policy implementation framework, which includes communication, resources, implementer disposition, and bureaucratic structure. The results showed that policy implementation had not been optimal, as indicated by uneven policy communication, limited resources and vaccine distribution, and suboptimal coordination among implementers, which impacted the low and fluctuating achievement of complete basic immunization coverage.